Reindustrialization in the conditions of new technological revolution: Road to the future - Sergey D. Bodrunov (Ural State University of Economics, 2019)
In today’s economy, technological leadership is the only way to overcome the gap and dependence on developed countries. The purpose of the paper is to show the necessity, conditions and results of the reindustrialization in Russia based on the latest technological advantages. The methodological basis of the research is the theories and concepts of technological development. The author applies general scientific methods of observation and collection of facts, analysis and synthesis, logical and retrospective analysis. The shifts in the material conditions of production highlight a qualitative increase in knowledge-intensity of production. The structure and the substance of human needs and the forms of production organization are also changing. This tendency can result in the displacement of human from material production. The criteria of economic rationality will be receding into the background, since they do not prevent man-made environmental degradation and do not ensure meeting the real, but not imaginary or pretended needs. Economy, therefore, will be replaced by noonomy that is a non-economic mode of organization of production activity. People from the outside will regulate production as the external sphere for them. Since human is eliminated the production process, social relationships will no longer be determined by human participation in production activities. The research results are of value when developing the fundamentals of new technological revolution and conceiving the role of reindustrialization in this context.